Effect of vitamin E supplementation to diet containing herbal mixture on performance and carcass quality of broiler chickens - Santoso, U.; Fenita, Y.; Kususiyah, Kususiyah (Universitas Bengkulu, 2021)
The present study was conducted to evaluate the effect of vitamin E supplementation to diet containing herbal mixture on performance, meat quality, hematological status and fat deposition of broiler chickens. Eighty 15-day-old female broilers were distributed into 2 treatment groups with 4 replications (10 female broilers of each replication) as follows. Feed with FSBL plus 1 g of turmeric and 2 g garlic (P1) and Feed of P1 plus vitamin E (P2). Vitamin E supplementation had no effect on performance, carcass weight, meat bone ratio, drip loss and cooking loss, gizzard, spleen, proventriculus, gallbladder, heart, caecum, intestine, fat depot in abdomen, sartorial, neck, heart, proventriculus, and liver as expressed by fatty liver score, blood triglyceride, cholesterol, LDL and HDL concentrations, moisture, and fat and ash contents of meats. However, it reduced liver weight, toxicity score, gizzard fat depot and meat protein. In conclusion, vitamin E supplementation to diet containg herbal mixture reduced meat protein, toxicity score, and gizzard fat depot.